Beyond free will: Understanding approaches to agency and their suitability for Bandersnatch-like titles - Haahr, Mads (My University, 2022)
When Bandersnatch (2018) was released on Netflix, interactive storytelling became accessible to a mainstream audience on a new scale. While this interactive film lets audiences make binary choices, the influence they have over the plot is limited, and at times the correlation between a choice and the resulting story is difficult to recognize. Although it can be argued that this constitutes a thematic design choice for this particular title, we think there is general room for improvement for this type of highly restrictive, branching structure film, in order to make the format applicable to a wider range of themes and stories. In this paper, Bandersnatch is examined as a representative of its format in order to develop and identify approaches to increasing agency. We use Hartmut Koenitz’s SPP model to understand the title and its format, and the hermeneutic strip extension to assess the perceived agency. Then, we introduce and examine potential approaches to increased agency from other interactive narratives to understand their adaptability and impact. Our discussion concludes that the most promising design idea for increased agency in Bandersnatch-like titles is invisible agency; an approach in which a player model is generated based on identifiable traits in the audience behaviour and used to select matching plotlines. This approach would allow audiences to see the results of their choices immediately, but also allow the impact of the choices to accumulate as the plot progresses, thereby increasing the overall sense of agency.
PUBLISHED
Keywords: Narrative momentum; Player model; Replayability; Kaleidoscopic form; Black Mirror Bandersnatch; Hermeneutics; Double-hermeneutic-circle; SPP model; Involuntary agency; Obscured agency; Invisible agency; Agency; IDN; Interactive digital narrative; Creative Technologies